ESTUDIOS SOBRE LAS RESPUESTAS CONVULSIVANTES EXPERIMENTALES Y SUS MODIFICACIONES II MECANISMOS NEURALES - ARROYO, S; ALVAREZ, JAVIER A; ALCALDE OBRADOR, S (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1943)
C pallida is one of apparently 3 species of Commelina found in the Valley of Mexico and in the Mexican district of Oaxaca It is an annual herbaceous plant with a high percentage content of water-soluble substances, and with a high proportion of tannins
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, RESPUESTAS, CONVULSIVANTES, EXPERIMENTALES, MODIFICACIONES, MECANISMOS, NEURALES; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA